Analysis of Students' Mathematical Literacy Skills Reviewed from Problem Solving Skills - Azima, Laely Astafiani; Rahayu, Wardani; Sovia, Anny (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2025)
This study aims to describe students' mathematical literacy skills reviewed from problem-solving skills in solving AKM-shaped questions. The method of this research is a qualitative descriptive study. This study was conducted in class 10 MAN 3 Jakarta Pusat and took 251 students as respondents. Data collection in this study was carried out by conducting problem-solving tests, mathematical literacy tests, and interviews. Based on the level of mathematics literacy achievement, students are grouped into 4 levels, namely, requiring special intervention, basic, professional, and advanced. While problem-solving skills are grouped into 3 categories, namely low, medium, and high. The results showed that most students, regardless of problem-solving skills category, were at “needing special intervention” level in mathematical literacy achievement. However, no students in the low problem-solving skills category reached the advanced level in mathematical literacy. Students often ignore the “looking back” step in problem solving. In fact, ignoring this step causes many students to make mistakes in the final results, including students with higher problem-solving skills. These results indicate the importance of teacher intervention in mathematics learning so that students are more careful and effective in solving problems.